Rapid Selection of Column Base Plates - Bird, William R. (Engineering Journal, 1976)
Over the past several years there have been a number of articles published proposing design aids for the rapid selection of column base plates. Although the design calculations as presented in the AISC Manual of Steel Construction, 7th Edition, are relatively simple, the selection of the optimum plate geometry cannot be determined directly and can be quite time consuming in a large steel structure. The previously presented design aids provided rapid solutions to the design problem, but sacrificed the accuracy of manual calculations. A graphical approach to the design will be presented in this paper, which provides rapid and accurate solutions to the design of steel bearing plates and can be expanded to cover all column sections and loading conditions. The design procedure recommended by the AISC assumes that the bearing pressure on the bottom of the plate is of uniform intensity and that the column load is uniformly distributed over an effective rectangular area equal to 0.95 times the depth of the column section by 0.80 times the column flange width. Thus, the required bearing area based on the relationship of column loading to allowable concrete bearing pressure is first determined and the plate geometry selected to satisfy this requirement. The plate thickness is then determined by treating that portion of the plate that projects beyond the "effective rectangle" as an inverted cantilever and solving for the required thickness.